European Yearbook / Annuaire Européen, Volume 71 (2023) (European Yearbook / Annuaire Européen, 2024)
The European Yearbook promotes the scientific study of nineteen European supranational organisations and the OECD. Each volume contains a detailed survey of the history, structure and yearly activities of each organisation and an up-to-date chart providing a clear overview of the member states of each organisation.